Guidance on Reading, Studying and Memorizing the Qur'an for Children in Cemara Kulon Village Using Digital Methods - Didik Himmawan; Sella Selviana (Aslim: Journal of Education and Islamic Studies, 2024)
Reading, reciting and memorizing the Qur'an is a conscious and earnest effort made to remember and absorb the reading of the holy book of the Qur'an which contains miracles into the mind so that it always remembers the words of God. Reading and reciting the Qur'an is a form of worship that has many advantages for salvation in the world and in the hereafter. The purpose of this community service is to implement Guidance for Reading, Reciting and Memorizing the Qur'an for Children in Cemara Kulon Village Based on Digital. Using counseling and mentoring methods, guidance for reading and reciting the Qur'an with an individual approach and practice. The lecture method when delivering material on tajwid using videos and PowerPoint and the Iqra Digital book media is used when guiding children in reading and reciting the Qur'an. Practice is carried out when children are given the task of memorizing letters using the ummi method. The result of this Community Service is an increase in the ability to read, recite and memorize the Qur'an for children in Cemara Kulon Village, successfully motivating and increasing understanding of reading the Qur'an and also fostering spirituality in children by providing an understanding of readings and memorizing the Qur'an, so that they can read fluently (correctly) according to the science of tajwid, seen from the final results of children's learning, namely a greater sense of liking and interest in something or a new activity using a digital method that is still rarely found by children in Cemara Kulon Village, making it easier for children to learn the Qur'an.